A Different Land of Opportunity: The Geography of Intergenerational Mobility in the Early Twentieth-Century United States - Tan, Hui Ren (Journal of Labor Economics, 2023)
Has the geography of intergenerational mobility in the United States changed over time? Constructing a large historical linked sample, I show that upward mobility in the early twentieth century was greater for those who grew up in the coastal and industrial regions, in contrast to more recent times, where mobility is higher among persons who were raised in the middle of the country. The historical patterns are not driven by imperfections in record linkage or measurement error in economic status.